Rock & Rails: Extending Multi-touch Interactions with Shape Gestures to Enable Precise Spatial Manipulations - Wigdor, Daniel; Benko, Hrvoje; Pella, John; Lombardo, Jarrod; Williams, Sarah (ACM Conference on Human Factors for Computing Systems (CHI), 2011, 2011)
Direct touch manipulations enable the user to interact with the on-screen content in a direct and easy manner closely mimicking the spatial manipulations in the physical world. However, they also suffer from well-known issues of preci-sion, occlusion and an inability to isolate different degrees of freedom in spatial manipulations. We present a set of interactions, called Rock & Rails, that augment existing direct touch manipulations with shape-based gestures, thus providing on-demand gain control, occlusion avoidance, and separation of constraints in 2D manipulation tasks. Using shape gestures in combination with direct-manipulations allows us to do this without ambiguity in detection and without resorting to manipulation handles, which break the direct manipulation paradigm. Our set of interactions were evaluated by 8 expert graphic designers and were found to be easy to learn and master, as well as effective in accomplishing a precise graphical layout task.